ANALISIS PERSEPSI MASYARAKAT TENTANG PELAKSANAAN TUGAS SATPOL PP DALAM PENERTIBAN PROTOKOL KESEHATAN PADA MASA NEW NORMAL DI WARNET SEPANJANG JALAN MANYAR SAKTI KOTA PEKANBARU - Zulnasri Zulnasri; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:. This research is motivated because there are still many cafe visitors who do not wear masks, when visiting the cafe there is no body temperature check and the seat at the cafe is at a distance that has been set by the government. This study aims to find out the public's perception of the implementation of security guard duties in controlling health protocols during the new normal period at internet cafes along Jalan Manyar in Pekanbaru City. In managing the data, the researcher used quantitative descriptive analysis. The sample of this study were 100 people. The data collection used by researchers is by using questionnaires, interviews, observation, documentation. Based on the results of the research conducted, the respondents who answered YES with an average of 40.42 people with a percentage of 40.42%, while those who answered NO with an average of 59.58 people with a percentage of 59.58%. It can be concluded in accordance with the answers that answered YES with a percentage of 40.42% in the answer range of 0% -50%. So it can be concluded that the Public Perception of the Implementation of Satpol PP Duties in Control of Health Protocols in the New Normal Period at Warnet along Jalan Manyar Sakti Kota Pekanbaru can be said to be "Not Good".Key Words: Perception, Satpol PP Implementation